2021
DOI: 10.1111/sms.14107
|View full text |Cite
|
Sign up to set email alerts
|

Mediators between physical activity and academic achievement: A systematic review

Abstract: Funding informationThis study was funded by FEDER funds. The funder had no role in the design and conduct of the study Background: Research has suggested the beneficial effects of physical activity (PA) on academic achievement (AA). However, the mechanisms underlying this influence remain unclear. Some proposed mechanisms include physiological, cognitive, psychological, and behavioral paths. This study aimed to analyze mediators between PA and AA in children and adolescents. Methods: Systematic search in Medli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 63 publications
0
14
1
1
Order By: Relevance
“…Previous literature suggests that weight status is a stronger mediator for female than male individuals given greater weight stigma for female individuals (14); however, this study found stronger evidence for mediation among female students through CRF. One possible explanation may be higher levels of attention-deficit/hyperactivity disorder-related hyperactivity among male students, suggesting that male students with higher CRF are more likely to experience academically hindering hyperactivity than female students with higher CRF (35).…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Previous literature suggests that weight status is a stronger mediator for female than male individuals given greater weight stigma for female individuals (14); however, this study found stronger evidence for mediation among female students through CRF. One possible explanation may be higher levels of attention-deficit/hyperactivity disorder-related hyperactivity among male students, suggesting that male students with higher CRF are more likely to experience academically hindering hyperactivity than female students with higher CRF (35).…”
Section: Discussioncontrasting
confidence: 89%
“…The same systematic review found mixed results for mediation by adiposity measures, including BMI (14). Of five studies looking at mediation by adiposity variables, two found an indirect association (14). Beyond mediation, the literature on BMI and CRF as predictors of AA also points to a stronger role for CRF (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os achados deste estudo apontam que o comportamento sedentário pode eventualmente ter uma influência positiva maior que a gerada pelas horas de prática da AF, o que deve ser olhado com muito critério. Além disso, a relação entre a atividade física e o desempenho escolar pode ser influenciado por outras variáveis, como a aptidão cardiorrespiratória, cognição, bem estar mental e outros comportamentos relacionados ao exercício, agindo como mediadores na associação (Visier-Alfonso et al, 2022) Vale destacar como ponto forte do presente estudo, a utilização de equipamentos de acelerometria ActiGraph GT3X+, provavelmente os mais utilizados em estudos científicos para a mensuração da atividade física (Migueles et al, 2017). De fato parece haver ainda inconsistências nos resultados oriundos de investigações conduzidas com medidas baseadas em equipamentos quando comparadas àquelas que utilizam medidas autorelatadas de AF (Marques et al, 2018).…”
Section: Discussionunclassified
“…One of the literature gaps reveals scarce and mixed findings on what factors mediate the association between PA and academic achievement. To date, the association between PA and academic achievement in youth has been suggested to be underlain by some mediators, such as physical fitness, adiposity, cognitive function, behaviour, and mental well-being [ 19 ]. To our knowledge, only four studies have investigated whether executive function mediated the association between PA and academic achievement in youth.…”
Section: Introductionmentioning
confidence: 99%